Wireless pneumatic transmission gear shifter and engine ignition starter and stopper (wireless g-shift) / Engr. Dr. Mohd Azman Abdullah … [et al.] - Abdullah, Engr. Dr. Mohd Azman; Abd Hamid, Muhammad Ali Imran; Tamaldin, Engr. Dr. Noreffendy; Mohd Nor, Azre (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
A wireless pneumatic transmission gear shifter and engine ignition starter and stopper is designed and developed. It consists of 49MHz radio control (RC) transmitter powered by 9V batteries and 1mA RC receiver which control a 12V, 3A relay. The relay is used to control a pneumatic valve which is connected to a 2-bar air compressor. A solenoid valve is used to push and pull the gear shifter mechanism. The valve is able to produce a force of 200N which is required to shift the gear. The RC unit also transmits signals to the engine ignition system which controls the engine start and stop operations.